The Role of Christian Ethics in Contemporary Political Philosophy - Antonia Janampa; Wahyuddin Noor (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
This article examines the influence of Christian ethical principles on modern political philosophy, particularly in addressing moral dilemmas in governance, human rights, and environmental stewardship. By analyzing key philosophical frameworks and scriptural teachings, the paper highlights the compatibility and tension between secular political theories and Christian moral theology. It also explores the role of Catholic social teaching in promoting justice, peace, and the common good.